"If Only I Did Not Have That Label Attached to Me": Foregrounding Self-Positioning and Intersectionality in the Experiences of Immigrant and Refugee Youth. (2nd October 2017) - Fruja Amthor, Ramona
Abstract : In order to bring forth the specific intricacies of the migration experience among comparatively understudied immigrant and refugee youth, this article bridges an intersectionality framework with multicultural education scholars' calls to flexibility and fluidity in conceptualizing culture and identity. Drawing on in-depth interviews, the analysis is anchored by two pervasive themes: (a) the dynamic nature of identity positions whose intersections make the adaption of youth irreducibly nuanced and (b) the need for self-definition in the process of adaptation. Racial and ethnic positioning, national origin, class, legal status, and religion intersected in the participants' lives in important ways, but they did not fulfill the same role across the cases. Attention to how these social locations intersect offers insight into the importance of context-based examinations of immigrant youth positioning, in addition to the centrality of structural analyses. Taking on an intersectionality lens, educators can engage both with the need to examine newcomer youth's situations structurally, while also tuning in to their interpretations, local contexts, and how various structural positions are foregrounded or obscured in their immigrant and refugee students' paths.